Analisa Keekonomian Sumur “D” dan “Y” Lapangan “NOAM” Pada Penggunaan Electrical Submersible Pump (ESP) - Agnes Triana Pamassangan; Deny Fatryanto; Jan Friadi Sinaga; Karnila Willard; Firdaus; Luthfiyah Atisa Fadhilah (Pascasarjana Institut Agama Islam Sunan Giri Ponorogo, 2023)
The oil and gas industry has an important role in the country, namely as a source of national budget revenue and as an energy provider. To meet the energy supply, it is sought to maximize production in the existing oil and gas field, so that an artificial lift of the Electrical Submersible Pump is carried out in the “D” and “Y” wells of the “NOAM” field. This study was conducted to calculate and analyze the economics of the “D”and “Y” wells of the “NOAM” field in the Electrical Submersible Pump project to determine whether the project is profitable to continue or not, and to find out what economic parameters can affect the profit. The results of the economic analysis of the “D” and “Y” wells, obtained from the “D” well, namely NPV of 4,009,400 USD, IRR value of 44.42% and POT value of 1.43 years. Meanwhile, the “Y” well obtained NPV -2,329,510 USD, IRR -24.62% and POT 3.07 years. From the sensitivity results using spider diagrams that have been carried out at the “D” well, the increase in total production and oil prices affects NPV and NCF, IRR is influenced by production, Capex, and oil prices and for GOI Take is influenced by Opex and oil prices. Whereas in well “Y”, production, Capex and oil prices affect NPV, IRR and NCF and GOI Take is not affected by changes in economic elements. From the results of the calculation and sensitivity analysis, the use of Electrical submersible Pump is economical to continue in well “D” while in well “Y” it is not economical to continue.